Efficacy of an Alcohol Solution Prepared From the Roots of the Horse in Wounds of Horses (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
In the article, the effectiveness of an alcohol solution prepared from the root of the mullein in the treatment of wounds is clearly explained through experiments and observations.